EVALUASI KEBIJAKAN STANDAR PELAYANAN MINIMAL DI PUSKESMAS NAGRAK KABUPATEN SUKABUMI - Alda Adela Putri; Andi Mulyadi; Rizki Hegia Sampurna (Jurnal Governansi, 2022)
ABSTRACT Minimum service standards (SPM) are provisions for public services to meet all citizens’ basic needs. Based on observations and interviews conducted with several informants in this study, it was stated that the implementation of health services at the Nagrak Health Center, Sukabumi Regency, had not achieved the fulfilment of targets by the provisions of the SPM, meaning that the Nagrak Health Center had not met the standards in its services. This study intends to evaluate the Minimum Service Standards policy at the Nagrak Health Center, Sukabumi Regency. The research method used by the researcher is qualitative. In the setting of the informants, the researcher used purposive sampling, which consisted of 9 informants. Data collection techniques in this study used observation, interviews, and documentation. Data analysis techniques that will be used in this research are data reduction, data presentation, conclusion drawing and verification. The results showed that the MSS policy was very appropriate by providing a good impact on the Nagrak Health Center, the community, and the relevant Government.